Drug manufacturing and access to medicines: the West African story. A literature review of challenges and proposed remediation - Abigail A. Ekeigwe (SpringerOpen, 2019)
Abstract It is the right of all humans to have access to safe, quality and effective medicines. This article seeks to expound on the problems of drug manufacturing and challenges of accessing medicines in West Africa, and evaluate the strategies being adopted by international developmental partners and the governments to address them. West Africa is uniquely diverse in culture (having English, French and Portuguese speaking people) but generally affected by the same diseases (e.g., malaria, HIV/AIDS, and Tuberculosis). In this developmentally beleaguered region, drug development and manufacturing are still stuck in their embryonic stages where medicine distribution is chaotic and insufficiently regulated. An enduring question is why investment in research and development in medicines for neglected tropical diseases and manufacturing is still very low in Africa and in particular West Africa. In this article, we look at how these vulnerabilities are exploited by unscrupulous merchants, leading to massive influx of fake and substandard medicines to the supply chain, making it difficult for the rural, voiceless poor to access quality safe medication. Through an examination of current research and published works by the World Health Organization (WHO), the United States Pharmacopeia (USP) and other international development partners in Africa, first hand interactions with manufacturers, medicine regulators, regulatory consultants, and the patients, as well as from personal observations, the article crystallizes the major issues and challenges to drug manufacturing and access to quality, safe, and effective essential medicines in West Africa. This article also examines the strategies and policies being implemented to salvage the situation. It is irrevocably clear that solving the challenges of providing safe medication to West Africa is a collective responsibility - the government (through legislation, strategic regulations and policies), medicines manufacturers (adoption of Good Manufacturing Practices and ethics), regulators (through persuasion and enforcement of rules), regulatory consultants, the patients (empowered, informed about their rights and courage and willingness to report drug reactions and discernible counterfeiting), the international development partners and all other stake holders in the health care sector have roles to play in ensuring that the public has access to quality safe and efficacious medicines.